2017
DOI: 10.1021/acs.biochem.7b00772
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Role of Ser26 Hydrogen Bonding in Aβ42 Assembly and Toxicity

Abstract: Amyloid β-protein (Aβ) assembly is a seminal process in Alzheimer's disease. Elucidating the mechanistic features of this process is thought to be vital for the design and targeting of therapeutic agents. Computational studies of the most pathologic form of Aβ, the 42-residue Aβ42 peptide, have suggested that hydrogen bonding involving Ser26 may be particularly important in organizing a monomer folding nucleus and in subsequent peptide assembly. To study this question, we experimentally determined structure-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(27 reference statements)
1
1
0
Order By: Relevance
“…This is in agreement with an earlier experimental study which reported that the G25P mutation not only inhibits the aggregation of Aβ 1-42 but also prevents the neurotoxicity induced by this peptide [36]. A number of previous studies have reported the significance of region 23-28 in Aβ fibril formation [28][29][30]. Accordingly, the α-strand structure formed by residues 24-26 may have substantial importance in Aβ aggregation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in agreement with an earlier experimental study which reported that the G25P mutation not only inhibits the aggregation of Aβ 1-42 but also prevents the neurotoxicity induced by this peptide [36]. A number of previous studies have reported the significance of region 23-28 in Aβ fibril formation [28][29][30]. Accordingly, the α-strand structure formed by residues 24-26 may have substantial importance in Aβ aggregation.…”
Section: Discussionsupporting
confidence: 92%
“…This demonstrates the possibility of extension of the α-strand region 24-26 (VGS). Several studies have reported the importance of region 23-28 in Aβ fibril formation [28][29][30]. Accordingly, the occurrence of α-strand in region 24-26 may have substantial importance.…”
Section: Occurrence Of α-Strand Structure In Region 24-26mentioning
confidence: 99%